IP-over-WDM network design methodology to improve efficiency in overall expenditure due to cost and energy consumption - Dey, Suman Kr; Adhya, Aneek (Journal of optical communications and networking, 2015)
With the rapid growth of traffic volume in telecom networks, a larger amount of network equipment with higher capacity and enhanced processing speed is required to accommodate the traffic. Therefore, expenditure due to cost and energy consumption (EC) of network equipment is also increasing. In existing research toward improving efficiency in spending, during the greenfield network design phase (i.e., the network planning phase or the phase wherein capacity is provisioned for a new network), either cost efficiency or EC efficiency is considered. However, the most cost-efficient network may not always be the most energy- efficient. Thus, during the network planning phase, the cost andECof network equipment should be considered together for cost- and energy-optimized realization of the network. In this study, an IP-over-WDM(IPoWDM) network design is explored to reduce the combined expenditure (due to cost and EC of network equipment) for setting up and operating the network over a given time period (referred to as the planning period). In this regard, we propose mixed integer linear programming-based optimization models and auxiliary matrix-based cost- and energy-efficient network design (AM-CEND) heuristic to minimize the overall expenditure. In the proposed schemes, network equipment is provisioned judiciously such that the overall expenditure is minimized. In this regard, we use a practical network setting, where all network equipment is considered to be bidirectional, and WDM equipment is considered with finite maximum transparent reach limits. It may be observed that a network designed using AM-CENDheuristic offers significant savings in the overall expenditure as illustrated by our exhaustive simulation study conducted for the example network scenario.